Fluorescent sensors reporting the activity of ammonium transceptors in live cells - De Michele, Roberto; Großmann, Guido (eLife, 2013)
A modified form of Green Fluorescent Protein integrated into an ammonium transporter provides a sensor that can be used to monitor transport activity in vivo.